Etnobotani Tanaman Aromatik Suku Melayu Sambas Sebagai Sumber Belajar Kontekstual Biologi SMA: (Ethnobotany of Aromatic Plants of The Malay Sambas Tribe as a Conetxtual Learning Resource for High School Biology) - Sandi, Friti May; Rahayu, Hanum Mukti; Sunandar , Ari (BIODIK, 2024)
The Sambas Malay tribe utilizes aromatic plants for traditional, medicinal, and culinary purposes. This research aims to identify the aromatic plant species used by the Sambas Malay tribe and evaluate their potential as a biology learning resource. Using an ethnographic approach with qualitative methods, data were collected through interviews, observations, documentation, identification, and questionnaires. The results revealed 26 species from 18 plant families that are used in the traditional, medicinal, and culinary practices of the Sambas Malay tribe. These aromatic plants were considered valuable as a biology learning resource, receiving a score of 72% based on responses from teachers. This material can be applied in biodiversity lessons for 10th-grade high school students (SMA). Abstrak. Suku Melayu Sambas memanfaatkan tanaman aromatik untuk tradisi, pengobatan, dan kuliner. Penelitian ini bertujuan untuk mengidentifikasi spesies tanaman aromatik yang digunakan oleh suku Melayu Sambas dan menilai potensinya sebagai sumber belajar biologi. Menggunakan pendekatan etnografi dengan metode kualitatif, data dikumpulkan melalui wawancara, observasi, dokumentasi, identifikasi, dan angket. Hasil penelitian menunjukkan bahwa 26 spesies dari 18 famili tumbuhan teridentifikasi dalam tradisi adat, pengobatan, dan kuliner suku Melayu Sambas. Tanaman aromatik tersebut dinilai layak menjadi sumber belajar biologi dengan skor 72% berdasarkan angket respon dari guru. Materi ini dapat diterapkan dalam pembelajaran keanekaragaman hayati untuk kelas X SMA.